Quantum confined peptide assemblies with tunable visible to near-infrared spectral range - Kai Tao (Nature Portfolio, 2018)
Quantum confined (QC) materials have favorable photoluminescent properties, yet are less bioavailable. Here, the authors developed aromatic cyclo-dipeptides that assemble into quantum dots and organize into biocompatible QC supramolecular structures suitable for in vivo imaging and optoelectronics.